EFEKTIVITAS INFORMASI DAN EDUKASI PENGELOLAAN HUTAN MANGROVE BAGI MASYARAKAT KUALA LANGSA - Nurul Najmi; Eka Lisdayanti; Rahmawati Rahmawati; Fadli Afriandi; Ligar Abdillah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2024)
Mangroves have a very strategic function for coastal communities ecologically, socially, and economically. Important information about Kuala Langsa mangrove forest management aims to educate coastal communities as the first users in utilizing environmental services in the form of mangrove tourism potential and managing coastal areas. Service activities are carried out to coastal communities living around the Kuala Langsa mangrove forest area. The activity involved 15 respondents consisting of Kuala Langsa mangrove forest ecotourism managers and coastal communities living around the area. The method carried out in this activity is surveys and interviews about management information and the potential of Kuala Langsa mangrove forests. The results of the activity showed that the community was very interested in participating in the activity marked by enthusiasm and warm discussion in the forum. People are more aware that no matter how small the damage done will have a big impact if done continuously. The community also agreed that waste can reduce beauty and reduce the population of fisheries and they agree that the healthier the mangroves can attract tourists and improve the economy of the surrounding community.